The use of Landscape Ecology as tools to asses the representation of protected areas and Indigenous lands in the ecoregion the north coast of Brazil - Ferreira, Leandro Valle; Cunha, Denise de Andrade; Leal, Darley Calderado (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2008)
This paper presents the application of the gap analysis using the actual mosaic of the strictly-use protected areas, sustainableuse proctected areas and indigenous lands in the study of the representation of the ecorregions along the North Coast of Brazil to identify gaps in this system and propose their expansion of protected areas.